3-D Front Reconstruction From Radarsat-1 SAR Data - Marghany, Maged; Hashim, Mazlan (2006)
This paper presents work done to utilize RADARSAT-1 SAR data to reconstruct 3-D of coastal water front. The velocity bunching model used to extract the significant wave height from RADARSAT-1 SAR while the Volttera model used to model the front movements. Bspline also is implemented to reconstruct the front into 3-D. This study shows that the integration between velocity bunching, Volttera models and B-spline can be used as geomatica tool for 3-D front reconstruction.